2017
DOI: 10.15376/biores.12.4.7784-7792
|View full text |Cite
|
Sign up to set email alerts
|

Wood-bamboo particleboard: Mechanical properties

Abstract: Mechanical characteristics were evaluated of wood-bamboo-based particleboard having the proportions of 100% wood and 0% bamboo, 75% wood and 25% bamboo, and 50% wood and 50% bamboo. This particleboard used Eucalyptus urophylla × grandis wood, Dendrocalamus asper bamboo, and castor oil-based polyurethane resin. Through destructive testing, the values of perpendicular tensile, static bending, modulus of elasticity, and screw pullout strength in the top and face surfaces were analyzed. For 0%, 25%, and 50% bamboo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 8 publications
0
8
0
1
Order By: Relevance
“…Contudo, segundo MOTA et al [25] os valores de densidade para as diversas espécies de bambu podem sofrer variações, inclusive dentro da mesma espécie, principalmente devido a idade e estrutura anatômica. Com isso, a densidade é um parâmetro que depende principalmente do conteúdo, espessura da parede das células e diâmetro das fibras, sendo que espécies com densidade básica mais baixa apresentam fibras mais finas [26,27]. O valor de densidade básica influencia na quantidade de partículas utilizadas para produção do compósito, pois está diretamente relacionado com a sua massa.…”
Section: Propriedades Físicas Valorunclassified
“…Contudo, segundo MOTA et al [25] os valores de densidade para as diversas espécies de bambu podem sofrer variações, inclusive dentro da mesma espécie, principalmente devido a idade e estrutura anatômica. Com isso, a densidade é um parâmetro que depende principalmente do conteúdo, espessura da parede das células e diâmetro das fibras, sendo que espécies com densidade básica mais baixa apresentam fibras mais finas [26,27]. O valor de densidade básica influencia na quantidade de partículas utilizadas para produção do compósito, pois está diretamente relacionado com a sua massa.…”
Section: Propriedades Físicas Valorunclassified
“…Bamboo was found to be a good reinforcing material for particleboard. De Almeida et al [ 20 ] reported that the incorporation of 25% and 50% of Dendrocalamus asper bamboo into particleboard made of Eucalyptus urophylla × grandis wood had improved the bending strength of the particleboard produced. Mixing a more compressible wood with other noncompressible wood could enhance the compression and consolidation of the particleboard [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, particleboard is an effective method to utilize various biological resources, and various related studies have been reported. De Almeida et al (2017) made the wood-bamboo-based particleboard and evaluated its mechanical properties. Bekhta et al (2013) evaluated the properties of the wood-straw-based particleboard.…”
Section: Introductionmentioning
confidence: 99%